Rational design and evaluation of HBsAg polymeric nanoparticles as antigen delivery carriers - Dewangan H.K.; Pandey T.; Maurya L.; Singh S. (My University, 2025)
The present work is focused on the development and evaluation of single dose sustained-release Hepatitis B surface antigen (HBsAg) loaded nanovaccine for Hepatitis B. The conventional treatment suffers from repeated administration and hence requires a booster dose. Therefore, polymeric nanovaccine of HBsAg was developed by double emulsion solvent evaporation technique, utilizing central composite design for formulation optimization. The effects of independent variables (like polymer amount, stabilizer concentration, aqueous/organic phase ratio and homogenizer speed) were also studied on critical quality attributes like particle size and entrapment efficiency. Nanovaccine was characterized in terms of physicochemical parameters, release, internalization and in vivo immunological evaluation in BALB/c mice after administration by different routes such as oral, sub-cutaneous, nasal and intramuscular. The designed nanovaccine demonstrated nanometric size with smooth surface, negative zeta potential, maximum entrapment, sustained release and better internalization in macrophage and MRC-5 cell line. The immune-stimulating activity of nanovaccine administered by different routes was evaluated by measuring anti-HBsAg titre like specific immunoglobulin IgG and IgA response and cytokine level (interleukin-2, interferon-Y) measurement. The results indicated that the nanovaccine administered by intramuscular route produced better humoral as well as cellular responses and potential carriers for antigen delivery at single dose administration via intramuscular route. © 2018